A Critical Review on the Book Stone Tools in Human Evolution, Behavioral Differences among Technological Primates by John Shea - Elham Ghasidian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In his book Stone Tools in Human Evolution, Behavioural Differences among Technological Primates, John Shea focuses on a new framework for analyzing stone tools to answer questions related to the evolution of human behavior. Although stone tools have great potential for understanding human evolution, the traditional archaeological approaches in analysis, biased our understanding on human evolution through them. Shea emphasizes that archaeologists must change their traditional approach and find new ways to study human evolution and behavior based on stone tools. This novel method will bring together palaeoanthropologists, palaeogeneticists and archaeologists and lead to a better understanding of the human behavior and evolution. The present paper tries to evaluate this new approach and see how close it is to achieve this goal. Reviewing the book shows that there is still a long way to go to understand human behavior and evolution through the study of stone tools. The book ends with many open questions, leaving readers wondering whether the author was able to tackle the traditional archaeological approach which Shea himself has been critical of throughout the book.